Digital Competences and Education - Levano-Francia, Luz (2019)
This article provides an analysis of digital competences in the current context. The growing expectation of new technologies and their multiple applications have produced important repercussions in all spheres of society, and, specifically, in the aspect of higher education where the demands are more than significant seeking to cover their implications. In the first place, the theoretical panorama about the different meanings and concepts in relation to digital competences is made known. This approach provides information on aspects that relate to digital s. Next, below there are some data that allow to give new perspectives, such as the importance and repercussions, as well as what should be the digital competences in professors according to the current demand in higher education. Finally, a variety of expectations are presented in relation to the aspects that could be developed based on such a relevant topic.